Development of an indoor air quality checklist for risk assessment of indoor air pollutants by semiquantitative score in nonindustrial workplaces - Syazwan AI; Rafee BM; Hafizan J; Azman AZF; Nizar AM; Izwyn Z; Muhaimin AA; Syafiq Yunos MA; Anita AR; Muhamad Hanafiah J; Shaharuddin MS; Ibthisham AM; et al. (Dove Medical Press, 2012)
AI Syazwan1, B Mohd Rafee1, Juahir Hafizan2, AZF Azman1, AM Nizar3, Z Izwyn4, AA Muhaimin5, MA Syafiq Yunos6, AR Anita1, J Muhamad Hanafiah1, MS Shaharuddin1, A Mohd Ibthisham7, Mohd Hasmadi Ismail8, MN Mohamad Azhar1, HS Azizan1, I Zulfadhli9, J Othman101Department of Community Health, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, Selangor, Malaysia; 2Department of Environmental Science, Faculty of Environmental Studies, Universiti Putra Malaysia, Selangor, Malaysia; 3Pharmacology Unit, Department of Human Anatomy, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, Selangor, Malaysia; 4Department of Therapy and Rehabilitation, Faculty of Health Science and Biomedical Engineering, Universiti Teknologi Malaysia, Johor, Malaysia; 5Department of Environmental Management, Faculty of Environmental Studies, Universiti Putra Malaysia, Selangor, Malaysia; 6Plant Assessment Technology (PAT), Industrial Technology Division (BTI), Malaysian Nuclear Agency (Nuklear Malaysia), Bangi, Kajang, Malaysia; 7Department of Mechanical Engineering, Faculty of Mechanical Engineering, Universiti Teknologi Malaysia, UTM Skudai, Johor, Malaysia; 8Department of Forest Production, Faculty of Forestry, Universiti Putra Malaysia, Selangor, Malaysia; 9Faculty of Built Environment and Architect, Universiti Teknologi Malaysia, Skudai, Johor, Malaysia; 10Department of Counsellor Education and Counselling Psychology (DCECP), Faculty of Educational Studies, Universiti Putra Malaysia, Selangor, MalaysiaBackground: To meet the current diversified health needs in workplaces, especially in nonindustrial workplaces in developing countries, an indoor air quality (IAQ) component of a participatory occupational safety and health survey should be included.Objectives: The purpose of this study was to evaluate and suggest a multidisciplinary, integrated IAQ checklist for evaluating the health risk of building occupants. This IAQ checklist proposed to support employers, workers, and assessors in understanding a wide range of important elements in the indoor air environment to promote awareness in nonindustrial workplaces.Methods: The general structure of and specific items in the IAQ checklist were discussed in a focus group meeting with IAQ assessors based upon the result of a literature review, previous industrial code of practice, and previous interviews with company employers and workers.Results: For practicality and validity, several sessions were held to elicit the opinions of company members, and, as a result, modifications were made. The newly developed IAQ checklist was finally formulated, consisting of seven core areas, nine technical areas, and 71 essential items. Each item was linked to a suitable section in the Industry Code of Practice on Indoor Air Quality published by the Department of Occupational Safety and Health.Conclusion: Combined usage of an IAQ checklist with the information from the Industry Code of Practice on Indoor Air Quality would provide easily comprehensible information and practical support. Intervention and evaluation studies using this newly developed IAQ checklist will clarify the effectiveness of a new approach in evaluating the risk of indoor air pollutants in the workplace.Keywords: action checklist, aggregated risk index (ARI), qualitative, reliability, SME, enterprise, indoor environmental quality (IEQ), sick building syndrome, indoor air quality assessment